Members’ willingness to pay for sustainability agricultural organization: A Heckman model approach - Topuz, Bakiye Kilic (Emirates Journal of Food and Agriculture, 2023)
The purpose of this research analyzed the factors influencing the members’ willingness to pay capital in the agricultural cooperatives and unions. The research was performed on a sample 155 members of agricultural organizations in Igdir province of Türkiye using the Simple Random Sampling method. Members’ willingness to pay capital to their organizations were examined using the Contingent Valuation Method and effected factors were analyzed by Heckman Sample Selection model. The research showed that 56.6% of members were willing to pay capital an average of 131 for sustainability of organizations. According to the model results showed that members’ gender, agricultural income, know definition of organization, increase in income of members, pay entry capital, frequency of visiting, meeting the general assembly, cohesion of members positively affected, however, age, household, animal units, negative experience in the past with their organizations negatively affected the members’ willingness to pay capital. In order to sustainable of agricultural organizations, cohesion of members and participation to general assembly must increase. And, encouraging more young and female farmers to become a member, taking an active role cooperatives and unions in marketing and supply input could increase the members’ willingness to pay capital. In addition, training programs should be organized by agricultural organizations and government about increasing capital and economic participation. Keywords: Agricultural organizations; Contingent analysis; Cooperative; Heckman sample selection model; Willingness to pay capital